The Effect of Floor Gymnastics Exercises on Body Movement Flexibility in Fifth Grade Students at SDN 9 Jambu Mlonggo Jepara - Ibawi, M. Mahfud; Efendi, Abdullah (Jurnal Gentala Pendidikan Dasar, 2025)
This study investigates the effect of floor gymnastics training on body movement flexibility among fifth-grade students at SDN 9 Jambu Mlonggo, Jepara. Using a quantitative experimental approach with a one-group pretest–posttest design, a total of 25 students were selected through total sampling. The independent variable was floor gymnastics training, while the dependent variable was body movement flexibility measured by the sit-and-reach test over six consecutive weeks. Statistical analysis using the Paired Sample t-test revealed that flexibility improvements were not significant in the first two weeks, indicating an initial adaptation phase. However, significant increases were observed starting from week four (p = 0.003) and continued to weeks five and six (p < 0.001), demonstrating the cumulative effect of structured and progressive training. These results highlight that sustained floor gymnastics practice enhances flexibility through neuromuscular adaptation and increased elasticity of muscles and joints. The findings reinforce the importance of incorporating continuous and progressive flexibility training within physical education programs, especially in the context of the Indonesian “Merdeka Curriculum” which emphasizes active, student-centered learning.